Misidentification of Carcharhinus galapagensis (Snodgrass & Heller, 1905) in the Southwest Pacific Ocean - Duffy, Clinton A. J. (Zootaxa, 2016)
Although primarily a coral reef species the grey reef shark Carcharhinus amblyrhynchos has been recorded from a number of subtropical oceanic islands and reefs in the Southwest Pacific Ocean. Examination of all nominal C. amblyrhynchos voucher material collected from Lord Howe Island, Elizabeth and Middleton Reefs and Norfolk Island resulted in the re-identification of these specimens as Galapagos sharks, C. galapagensis. As C. amblyrhynchos superficially resembles C. galapagensis visual records of C. amblyrhynchos from Elizabeth and Middleton Reefs and the Kermadec Islands cannot be substantiated without voucher material. Carcharhinus amblyrhynchos therefore appears to be confined to waters north of about 25o S in the Southwest Pacific. Precaudal vertebral counts should be used to confirm the identification of nominal C. amblyrhynchos specimens that have an interdorsal ridge.